2002
DOI: 10.1177/074873040201700308
|View full text |Cite
|
Sign up to set email alerts
|

Djungarian Hamsters: A Species with a Labile Circadian Pacemaker? Arrhythmicity under a Light-Dark Cycle Induced by Short Light Pulses

Abstract: In most cases, phase-shifting effects of light pulses are studied in animals kept in constant darkness (DD) or in animals released into DD following the stimulus. In this study, the authors exposed Djungarian hamsters (Phodopus sungorus) to short light pulses during the dark phase of a 16:8 light-dark (LD) cycle and thus obtained a type VI phase response curve. Light pulses early in the night caused phase delays of the activity onset as well as phase advances of the activity offset, whereas light pulses later … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
13
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(15 citation statements)
references
References 31 publications
2
13
0
Order By: Relevance
“…In accordance with our study, Lerchl [39] reported significant effects on melatonin amplitude and phase one night after a light pulse at midnight in the same species. However our results show that those alterations are still visible 2 days after the photic stimulus, fitting with results from Steinlechner et al [40] who showed that already short light pulses can have a long-lasting or even destructive effect on circadian rhythms. It is known as well that during resetting of the mammalian circadian clock, not only the clock's phase is shifted, but amplitude of overt rhythms driven by the clock may be temporarily reduced or even abolished [41].…”
Section: Discussionsupporting
confidence: 92%
“…In accordance with our study, Lerchl [39] reported significant effects on melatonin amplitude and phase one night after a light pulse at midnight in the same species. However our results show that those alterations are still visible 2 days after the photic stimulus, fitting with results from Steinlechner et al [40] who showed that already short light pulses can have a long-lasting or even destructive effect on circadian rhythms. It is known as well that during resetting of the mammalian circadian clock, not only the clock's phase is shifted, but amplitude of overt rhythms driven by the clock may be temporarily reduced or even abolished [41].…”
Section: Discussionsupporting
confidence: 92%
“…When temperatures are low and food is scarce, they may rely on heterothermy (prolonged torpor or hibernation) to save energy. Fat deposition also favors energy investment in later reproduction and thus enhances reproductive success in both sexes (e.g., Bronson, ; Geiser & Ruf, ; Steinlechner, Stieglitz, & Ruf, ). Over evolutionary time, small‐bodied mammals have often adjusted reproduction to annual day length (or photoperiod) fluctuations, predicting seasonal changes in temperature and food abundance.…”
Section: Discussionmentioning
confidence: 99%
“…PER1) feedback loops of clock genes that are expressed rhythmically and generate output signals such as vasopressin (AVP) release from the SCN or melatonin secretion from the pineal gland. This provides the organism with photoperiodic information and thereby determines torpor season (Pevet, 1988; Bartness & Goldman, 1989; Steinlechner et al ., 2002; Sumova et al ., 2003; Tournier et al ., 2003; Johnston et al . ; 2005).…”
Section: Introductionmentioning
confidence: 99%